Integrated Soil Fertility Management on Local Coconut Hybrid in a Farmer- Managed Coconut-Based Cropping System - Millicent I. Secretaria; Rogaciano Z. Margate (International Coconut Community, 2001)
An integrated soil fertility management or ISFM on-farm trial was conducted at Barangay Tawan-tawan, Baguio District, Davao City in 1993 to 1999 to know the effects of organic and inorganic fertilizers on the vegetative growth, nutrient status and yield performance of intercropped Catigan dwarf x Laguna tall (CATD x LAGT) coconut hybrid better known as PCA 15–1 or CATLAG. Vegetative growth of CATD x LAGT palms revealed that ammonium sulfate + NaCl and goat manure + NaCl produced significantly bigger girth size on the first year and more number of leaves and living fronds on the second and fourth year, respectively. These treatments also enhanced early flowering (>50% @ 4.5 years) and yield (51-53 nuts/tree/yr @) 5 years from field planting) in hybrid palms. The organic fertilizers, i.e. goat manure and coconut husk, become more effective in their effect on the vegetative and reproductive characters of palms when combined with a Cl source (NaCl). The application of Cl nutrient contributed to the better performance of palms during the drought condition. The application of goat manure resulted in improved levels of soil nutrients as K, Ca, Mg and P, increased percent base saturation and lower soil acidity. The use of local hybrid, PCA 15-1 and ISFM-based low cost production inputs such as ammonium sulfate, goat manure/coco waste (husk) and common table salt as well as intercropping suitable crops under young coconuts is a profitable package of technologies capable of improving and sustaining coconut farm productivity in the Philippines.